Helicopter Parenting: A Review - Bannayeva, Almaz; Sarandöl, Aslı (Psikiyatride güncel yaklaşimlar, 2025)
Helicopter parenting is defined as overprotective, overcontrolling and perfectionist parental attitudes that are obsessively interested in all aspects of their children's lives. In recent years, with the development of technology, helicopter parenting has become more common. Although helicopter parents behave these attitudes to protect the well-being of their children, studies show that helicopter attitudes mainly negatively affect children's development and these individuals experience more difficulties in the future. The aim of the study is to contribute to the literature by bringing together studies examining helicopter parenting attitudes and the effects of these attitudes on individuals' lives and to offer suggestions for experts working on this subject. In the article firstly, studies on the concept of helicopter parenting, its history and the assessment of helicopter attitude are reviewed. Then, the characteristics of parents with helicopter attitudes, the factors that trigger the emergence of this attitude, and research on the differentiation of helicopter attitudes in terms of parents and children were examined. Finally, studies examining the effects of helicopter attitudes on the development of the individual and these attitudes relationship with psychopathologies were compiled.